Formulation and characterization of chitosan hydrochloride and carboxymethyl chitosan encapsulated quercetin nanoparticles for controlled applications in foods system and simulated gastrointestinal condition. (November 2018) - Yan, Ling; Wang, Rongrong; Wang, Huimin; Sheng, Kangliang; Liu, Changhong; Qu, Hao; Ma, Aijin; Zheng, Lei
Abstract: Quercetin (QUE) has attracted widespread attention in food industries because of its potential bioactive functions. However, the application of QUE is quite limited due to its poor water solubility, stability and bioavailability. In this work, we constructed QUE-loaded chitosan hydrochloride (CHC) and carboxymethyl chitosan (CMCN) nanoparticles through electrostatic interaction, in order to enhance the bioavailability of QUE in functional foods and dietary supplements. At the optimal ratio (CMCN:CHC = 2.0 mg/mL:1.0 mg/mL), QUE-loaded CHC-CMCN nanoparticles (QUE-CDNPs) exhibited an average size of 386.3 ± 10.1 nm, zeta potential of −21.5 ± 1.0 mV, polydispersity index of 0.122 ± 0.03 and encapsulation efficiency of 70.0% ± 5.3%. The efficacy of successful QUE delivery of the prepared nanoparticles was examined by SEM, FT-IR and XRD. The QUE-CDNPs were found capable of controlled release of QUE for ten successive days in 50% ethanol, water-oil (50:50) simulants or 95% ethanol and whisky. QUE release was relatively higher in 50% ethanol, water-oil (50:50) simulants or whisky with higher DPPH scavenging activity than that of QUE-CDNPs in 95% ethanol. These results indicated that the enclosure of QUE in CDNPs improved its chemical stability and solubility, and had higher biological activity as assessed by antioxidant properties in 50% ethanol, water-oil (50:50) simulants or whisky systems. Furthermore, we confirmed that only a partial release of QUE from CDNPs was provoked in gastric fluid condition, whereas in intestine fluids, QUE showed a release as high as ca. 86%. Our study suggests that the CDNPs may be utilized to control the release of QUE in the gastro-intestinal condition and three food systems (i.e. 50% ethanol, water-oil (50:50) simulants or whisky systems), and this simple approach can be applied to other bioactive compounds with low aqueous solubility. Graphical abstract: Image 1 Highlights: CHC-CMC nanoparticles (CDNPs) successfully encapsulated quercetin (QUE). The release profile shows CDNPs delayed QUE degradation in four food system. The CDNPs were utilized to control the release of QUE in the GI condition. The simple method could be applied to other bioactive compounds with low solubility.